Analysis of Teachers' Difficulties in Implementing the Mathematics Learning Process at SDN 07 Kumbe, Bima City - Nurhasanah, Nurhasanah (Fusshilat : Jurnal Studi Pendidikan dan Keislaman, 2024)
Abstract : This study aims to uncover the various challenges faced by teachers in the teaching process at SDN 07 Kumbe, Bima City. Data were collected through structured interviews and documentation. The results of the study reveal several difficulties experienced by teachers in mathematics learning, namely: 1) lack of student interest in the subject of mathematics; 2) students' reluctance to memorize formulas; 3) differences in the past and present learning systems; 4) the use of thematic books that are less effective for mathematics learning; and 5) teachers' difficulties in developing the material contained in the books. Proposed solutions to overcome these difficulties include: 1) Teachers should provide learning motivation to students; 2) use appropriate learning media; 3) apply mixed methods in the learning process, and 4) actively participate in teacher working groups (KKG). Abstrak : Penelitian ini bertujuan untuk mengungkap berbagai tantangan yang dihadapi oleh guru dalam proses pengajaran di SDN 07 Kumbe, Kota Bima. Data dikumpulkan melalui wawancara terstruktur dan dokumentasi. Hasil penelitian mengungkapkan beberapa kesulitan yang dialami oleh guru dalam pembelajaran matematika, yaitu: 1) kurangnya minat siswa terhadap mata pelajaran matematika; 2) siswa enggan menghafal rumus; 3) perbedaan sistem pembelajaran dulu dan sekarang; 4) penggunaan buku tematik yang kurang efektif untuk pembelajaran matematika; dan 5) kesulitan guru dalam mengembangkan materi yang ada dalam buku. Solusi yang diusulkan untuk mengatasi kesulitan ini meliputi: 1) Guru harus memberikan motivasi belajar kepada siswa; 2) menggunakan media pembelajaran yang tepat; 3) menerapkan metode campuran dalam proses pembelajaran; dan 4) aktif berpartisipasi dalam kelompok kerja guru (KKG).